PENGARUH PROGRAM KAMPUS MENGAJAR ANGKATAN 6 TERHADAP PEMBENTUKAN KOMPETENSI PEDAGOGIK MAHASISWA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR UNIVERSITAS ISLAM RIAU - Damanik, Anggi Nur Rahayu; Ramadan, Zaka Hadikusuma (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to examine the effect of the Kampus Mengajar Program Batch 6 on the development of pedagogical competence of elementary school teacher education students at Universitas Islam Riau. This quantitative study employed a survey method. The population consisted of 74 alumni of the Kampus Mengajar Batch 6 in 2023, and total sampling was applied, resulting in 74 respondents. Data were collected using a questionnaire and analyzed through simple linear regression to determine the influence of the independent variable on the dependent variable. The results indicate that the Kampus Mengajar Program has a positive and significant effect on students’ pedagogical competence. This is supported by the regression analysis, showing a significance value of 0.000 < 0.05, confirming that participation in the program positively contributes to the development of pedagogical competence among PGSD students at Universitas Islam Riau.